Rediscovery of Aquilaria rostrata (Thymelaeaceae), a species thought to be extinct, and notes on Aquilaria conservation in Peninsular Malaysia - Lee, Shiou Yih; Mohamed, Rozi (Naturalis Biodiversity Center, 2016)
After more than 100 years since the first discovery, Aquilaria rostrata, a critically endangered species listed in the IUCN Red List and presumably extinct, has been rediscovered in Terengganu State of Peninsular Malaysia. Here, we describe the history, taxonomy, ecology and conservation status of this endemic species, and compare our findings with the species description made from the first and only collection produced prior to this study. In addition, we present the similarities between A. rostrata and several Aquilaria species occurring in Peninsular Malaysia and neighbouring regions using molecular sequence data from the nuclear ribosomal DNA (Internal Transcribed Spacer) and chloroplast intergenic spacer region (trnL-trnF). Our morphological and sequence analyses support the separate status of A. rostrata, a long-lost endemic species of Malaysia.